Application and Comparison of MAF-66 with AC and CMS in Vacuum Swing Adsorption Process for CO2 Capture from Flue Gas - M. Abdollahi; A.R. Sadri; Sh. Fatemi; M. Fakhroleslam (Iranian Journal of Chemical Engineering)
Vacuum swing adsorption (VSA) for CO2 capture has been a focus of significant research efforts aimed at developing innovative CO2 adsorbent materials. In this study, three adsorbents (MAF-66, AC, and CMS) were utilized for capturing CO2 from flue gas through the VSA process, and their performances were compared. The adsorption equilibrium and kinetics data were gathered from recent literature. A four-step VSA cycle was employed to assess the adsorbents' performance for CO2 capture, with a molar feed composition of CO2:N2 at 15:85%. Simulations of two-colums VSA lab-scales with different adsorbents were conducted. The operating conditions such as total feed flowrate, feed composition, feed pressure, temperature, and vacuum pressure were kept constant, and the impact of the adsorbent mass on recovery and productivity was analyzed. The simulation results indicated that both recovery and productivity decreased with increasing adsorbent mass. Furthermore, the necessary amount of each adsorbent to achieve a purity of 99.5% was determined. The modeling outcomes suggested that the VSA process employing MAF-66, CMS, and AC adsorbents would require 1.25, 3.19, and 8.2 grams of the adsorbent, respectively, to achieve N2 purity of 99.5%. Taking into account parameters such as recovery, productivity, and energy consumption, MAF-66 emerged as the most effective adsorbent in this study.